Os desastres e o Direito Ambiental: governança, normatividade e responsabilidade estatal - Barcessat, Ana Clara Aben-Athar (2017)
The so-called natural disasters have been the subject of much debate and study, both within and outside the field of Law. They entail, therefore, demands that require regulation, preferably in a more direct and effective way in the prevention and mitigation of the phenomena. In the present study, it has been chosen to use only the denomination 'disasters' due to the understanding that, although they have factors of natural origin in its causes, it is not possible to dissociate human action when these events occur. The main focus of this theoretical approach is the disasters that occur in Brazil, its most frequent causes, its most significant damages, the existing regulation in Brazil and in comparative Law, and the existence or not of effective legal accountability. To do this, research done in the institutes of Environmental Law is used, in view of its transversality with this branch of Law and in several fields of knowledge that surpass the orbit of Law, due to the understanding of the intrinsic interdisciplinarity in this matter and the necessity of the expansion of Its scope of action in the country, since disasters are events that generate, to a greater or lesser degree, destruction wherever they pass, impacting the environment, such as human relations, private goods and very often, even the survival of the populations on the affected sites